Statin Effects on Incidence, Treatment Success, and Mortality of Clostridium difficile Infections. (August 2020) - Gaviola, Marian L.; Scribe, Emily C.; Leverett, Haley N.; Howard, Meredith L.
Purpose: To review the effects of statin use in patients at risk for or diagnosed with Clostridium difficile infection (CDI) on CDI incidence, treatment success, and mortality. Methods: A literature search was performed through January 2019 using the following terms: statins, HMG-CoA inhibitors, Clostridium difficile, Clostridium difficile associated diarrhea, and Clostridium difficile infection. Additional references were identified from a review of literature citations. Studies evaluating statin effects on C difficile -related outcomes were included. Results: A total of 8 studies were identified for inclusion in this review. All studies were retrospective. Five studies reported the association between statin use and the development of CDI, suggesting that statins may decrease risk of CDI development in patients already on statin. In one study, there was an improved treatment response against CDI with the use of statin. Three retrospective studies evaluated statin use and mortality from CDI and only one study found significant mortality benefit in statin users. Conclusions: Statin use may have a protective effect against the development of CDI and improve CDI treatment success; however, it is unclear if use confers a mortality benefit. Current data remain sparse and larger, prospective studies are needed to confirm current results and identify the specific population that may benefit the most from this intervention.